Facilitating and Inhibiting Factors of Social Participation in the Elderly Based on Health-promoting Behaviors: A Cross-sectional Study - Mina Sharafi; Mohammad Mehdi Fadakar Davarani; Hamidreza Tohidi Nik; Arash Farvahari; Vahid Reza Borhaninejad (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives Social participation is a determining factor for promoting health and well-being. This study aims to investigate the factors facilitating and inhibiting the social participation of the elderly in Kerman, Iran based on their health-promoting behaviors. Methods & Materials This cross-sectional study was conducted on 276 elderly people over 60 years old in Kerman city in 2020. They completed a demographic from, the questionnaire of social participation based on the Canadian Community Health Survey, and the questionnaire of health- promoting behaviors. Descriptive statistics and statistical tests including univariate and multivariate regression were used for data analysis. Data were analyzed in SPSS software, version 26, and P<0.05 was considered statistically significant. Results The Mean±SD score of social participation was 6.71±4.01. Illness and health problems (50.3%), costs (39.1%), commuting problems (31.1%), low mood (29.3%), and COVID-19 pandemic (28.2%) were the most common barriers to social participation. The elderly who were single (P<0.001), younger (P<0.001), with academic degree (P<0.001), and low number of children (P<0.001) had significantly higher social participation. Multivariable analysis showed that physical activity (P=0.033), disease prevention (P=0.002), and physical and social health (P<0.001) were the factors affecting social participation of the elderly. Conclusion The social participation of the elderly in Kerman is affected by multiple factors. Therefore, planning to manage diseases, increase income, and solve the transportation problems of the elderly are recommended to improve their social participation.